Historical analysis of spanish competitiveness in the european framework: 19th and 20th centuries - PIRES, Luis (Papeles de Europa, 2011)
This article analyzes the evolution of Spanish competitiveness and economic growth during the 19th and 20th century. After defining the concept of competitiveness in relation with other notions like productivity, economic growth, comparative advantage, or international competition, we apply this concept to the Spanish experience. The study includes the evolution of the Spanish Gross Domestic Product in terms of its convergence and divergence, the historical contribution of labor, capital, and total factor productivity on Spanish development, the institutional contributions to growth, and the evolution of competitiveness in Spanish regions, clusters and companies. Among other conclusions, the article emphasizes that, since 1959, the progressive reduction of protectionism and intense public regulations, introduced at the end of the 19th century, allowed an intense economic growth and convergence process. But the Spanish economy still maintains some institutional shortcomings that reduce its potential future growth and affect its competitiveness and entrepreneurship.